A twisting story: how a single gene twists a snail? Mechanogenetics. Issue 4 (16th July 2015) - Kuroda, Reiko
Abstract: Left–right (l–r) symmetry breaking and the establishment of asymmetric animal body plan during embryonic development are fundamental questions in nature. The molecular basis of l–r symmetry breaking of snails is a fascinating topic as it is determined by a maternal single handedness-determining locus at a very early developmental stage. This perspective describes the current state of the art of the chiromorphogenesis, mainly based on our own work, i.e. the first step of l–r symmetry breaking, as proven by our "Mechanogenetics", before the start of zygotic gene expression, transfer of chirality information to the cell-fate determining stage, and the expression of nodal at the blastula stage. The Nodal signalling pathway is a common mechanism in vertebrates' chiromorphogenesis in later development. Studies on snails, especially Lymnaea ( L .) stagnalis, shall give important insights into the molecular basis of chiromorphogenesis not only in Lophotrochozoa but in vertebrates as well.